Sustainability spectacle and ‘post-oil’ greening initiatives - Koch, Natalie (Environmental politics, 2022)
Sustainability projects are being promoted around the world with a large dose of spectacle, including those in the Arabian Peninsula where governments have invested heavily in large greening projects and events. This article examines these spectacular projects in the United Arab Emirates (UAE), which are typically dismissed by Western observers as mere PR and ‘greenwashing.’ Moving past this simplistic critique, I contextualize ‘sustainability spectacle’ as a broad cultural phenomenon, with deep roots in Western countries. Based on ethnographic research on sustainability events, sites, and initiatives in the UAE, I show how ‘post-oil’ greening initiatives use sustainability spectacle to promote a positive narrative about the ‘modern’ national self, and reflect the growing international imperative to be green.
Gesehen am 05.12.2022